Political travel constraint: The role of Chinese popular nationalism. Issue 3 (24th March 2017) - Cheng, Mingming; Wong, Anthony IpKin; Prideaux, Bruce
ABSTRACT: This study extends the leisure constraint model by examining the role that popular nationalism has in Chinese outbound travel. Using a case study approach based on the 2012 Diaoyu/Senkaku Island Incident between China and Japan, the study demonstrates how Chinese popular nationalism has the potential to shape the geopolitical environment of all outbound Chinese tourism. The study proposes a new model that can be used to illustrate how popular nationalism may affect bilateral tourism in other settings. Findings of this study offer important insights for both scholars and practitioners contributing to the understanding of the impact of Chinese popular nationalism on bilateral tourism flows.